PRODUCTION COSTS, LEVELS OF SUBSIDIES AND PRICING IN NIGERIAN UNIVERSITIES, 2000 TO 2006 (2012)
Access to higher education, in relation to the production cost, is a key policy issue in Nigeria. To realise the high developmental impact of higher education on the country, a good understanding of how higher education price is affected by production cost and subsidy is necessary. Previous studies have analysed pricing in federal universities without considering its relationship to production cost and subsidies. This study, therefore, investigated the extent to which production cost and subsidy affect pricing in higher education in Nigeria. The study adopted the survey research design of ex-post facto type. Ten federal, seven state and three private universities were purposively sampled. Out of 2000 students selected through stratified random sampling method, 1000 were from the federal universities while 700 and 300 were from state and private universities respectively. Two instruments were used for data collection - Student Questionnaire on Pricing and Subsidy (r=0.84) for students; and the Nigerian University Expenditure, Revenue and Student Enrolment Questionnaire (r=0.75) used on the 20 Bursars, 20 Registrars, 20 Directors of Academic Planning, and 20 Directors of Works of the twenty sampled universities. Supplementary information was also collected from the National Universities Commission (NUC), Abuja. Five research questions were answered and three hypotheses tested. Descriptive Statistics, t-test, Multiple Regression and Analysis of Variance were employed for data analysis. There were significant differences in production costs among the three classified universities (F(2,18) = 29.59, p < 0.05). Federal universities had an average production cost of N119,421 between years 2000 and 2006 while the corresponding figures for state and private universities stood at N45,845 and N248,849 respectively. Significant differences were also found in the level of subsidy in the universities (F(2,18)=8.935, p<0.05). Subsidy was highest in the federal universities and was in the ratio of 57:45:10 among the federal, state and private universities respectively. The students‘ perceived level of subsidy was about half of what was found in these universities. Cost and subsidy had positive joint UNIVERSITY OF IBADAN LIBRARY v correlation with price (R=0.97). Cost (β=0.93) made higher contribution to price than subsidy (β=-0.30). Price was inelastic with respect to production cost (ε=0.82) and subsidy (ε=-0.36). The coefficients showed that higher education prices were more responsive to changes in production cost than subsidy, suggesting that changes in production cost caused higher changes in price than changes in subsidy. Production cost was directly related to price. Subsidy was however inversely related to price but its size was not big enough to cause a reduction in price. Increasing the quantum of subsidies employed will therefore result in price reduction and consequently increase student enrolment. Thus, government should enhance private sector participation through tax-deductable subsidies to reduce prices. NUC should also resuscitate its publications of Annual Review and Annual Report to improve access to information on universities by researchers. Key words: Education production cost, Education subsidies, Education pricing, Higher education, Nigerian universities. Word count: 495